Review on recent progress in WO3-based electrochromic films: preparation methods and performance enhancement strategies. Issue 1 (5th December 2022) - Zheng, Jin You; Sun, Qimeng; Cui, Jiameizi; Yu, Xiaomei; Li, Songjie; Zhang, Lili; Jiang, Suyu; Ma, Wei; Ma, Renzhi
Abstract : Typical preparation techniques and performance enhancement strategies for WO3 -based electrochromic films are described in detail in this review. Abstract : Transition metal oxides have drawn tremendous interest due to their unique physical and chemical properties. As one of the most promising electrochromic (EC) materials, tungsten trioxide (WO3 ) has attracted great attention due to its exceptional EC characteristics. This review summarizes the background and general concept of EC devices, and key criteria for evaluation of WO3 -based EC materials. Special focus is placed on preparation techniques and performance enhancement of WO3 EC films. Specifically, four methods – nanostructuring, regulating crystallinity, fabricating hybrid films, and preparing multilayer composite structures – have been developed to enhance the EC performance of WO3 films. Finally, we offer some important recommendations and perspectives on potential research directions for further study.